Strategic pathways to sustainable performance: The role of leadership, governance, and innovation in Indonesian local public services - Suskandari, Dyah; Fontana, Avanti; Pusparini, Elok Savitri (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines how transformational leadership fosters collaborative governance to enhance innovation and sustainable performance within Indonesian local governments. In decentralized systems, where authority and resources are dispersed, achieving coherence and innovation in public service delivery remains a major challenge. Using a quantitative explanatory approach, survey data were collected from public service organizations across Indonesian regions and analyzed through Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings reveal that transformational leadership directly strengthens collaborative governance and sustainable performance, while its influence on innovation performance is fully mediated by governance processes. Collaborative governance, in turn, enhances innovation capability and contributes to sustainability primarily when innovation performance is effectively realized. These results highlight a sequential interdependence among leadership, governance, and innovation in advancing sustainable outcomes. Innovation performance emerges as the critical mechanism through which leadership and governance translate into economic competitiveness, social inclusivity, and environmental responsibility. The study bridges micro-level leadership practices, meso-level governance mechanisms, and macro-level sustainability goals, offering practical insights for policymakers and public managers to strengthen collaborative frameworks and innovation capacity for accelerating sustainability in decentralized governance settings.